Characterization of international partnerships in global retinoblastoma care and research: A network analysis. - Hannah Girdler; Kaitlyn Flegg; John Prochaska; Helen Dimaras (Public Library of Science (PLoS), 2021)
Global cooperation is an integral component of global health research and practice. One Retinoblastoma World (1RBW) is a cooperative network of global treatment centers that care for children affected by retinoblastoma. The study aimed to determine the number, scope and nature of collaborations within 1RBW, and uncover how they are perceived to contribute towards improving retinoblastoma outcomes. A cross-sectional, mixed-methods egocentric network analysis was conducted. Treatment centers (n = 170) were invited to complete an electronic survey to identify collaborative activities between their institution (ego), and respective partners (alters). Network maps were generated to visualize connectivity. Key informants (n = 18) participated in semi-structured interviews to add details about the reported collaborations. Interviews were analysed through inductive thematic analysis. Surveys were completed by 56/170 (33%) of 1RBW treatment centers. Collectively, they identified 112 unique alters (80 treatment centers; 32 other organizations) for a total network size of 168 nodes. Most collaborations involved patient referrals, consultations and twinning/capacity building. Interviews identified four main themes: conceptualization of partnership; primary motivation for collaborations; common challenges to collaboration; and benefits to partnership. There is extensive global collaboration to reduce global retinoblastoma mortality, but there is room to expand connectivity through active efforts to include actors located at network peripheries.